Re: Futures : Studio Hani Rashid, University of Applied Arts Vienna - Rashid, Hani, 1958-; Luger, Sophie (Edition Die Angewandte, University Press., 2017)
"Hani Rashid, co-founder of Asymptote, the visionary New York architectural practice, has been heading up Studio Hani Rashid in Vienna since 2011. The curriculum focuses on the development of conceptual and practical skills for creating future-oriented architecture - on experimental investigation of atmospheric, phenomenal, and visual effects, which provides intelligent solutions for contemporary forms of dwelling and being but which should also satisfy 'feasibility criteria'. 'Re: Futures' uses texts, digital visualizations and descriptive architectural sketches to document the work created over recent years, and thereby reveals a spectrum of contemporary design methods and future-oriented architectural themes."--Provided by publisher